Thinking Globally, Acting Locally: Partiality, Preferences and Perspective - Oddie, Graham (Les ateliers de l'éthique / The Ethics Forum, 2014)
A rather promising value theory for environmental philosophers combines the well-known fitting attitude (FA) account of value with the rather less well-known account of value as richness. If the value of an entity is proportional to its degree of richness (which has been cashed out in terms of unified complexity and organic unity), then since natural entities, such as species or ecosystems, exhibit varying degrees of richness quite independently of what we happen to feel about them, they also possess differing degrees of mind-independent and subject-independent value. In particular, their value is not dependent on the desires or preferences of humans. The fitting attitudes account of value, at least as it is standardly developed, demands isomorphic evaluative responses on the part of all valuers. In particular, it entails that all valuers should have isomorphic preferences. But this seems absurd. I consider three different strategies with which the fitting attitude theorist can deflect this challenge. The first makes use of an account of non-standard value relations in terms of permissible preference orderings. The second appeals to value appearances and the associated notions of value distance and value perspective. The third involves an account of the ultimate bearers of value as properties, rather than as propositions or states of affairs. These strategies are not all mutually incompatible. While it isn’t possible to combine the first and second strategies, it is possible to combine the first and third strategies, and also to combine the second and the third.